2022
DOI: 10.1088/1361-648x/ac44d2
|View full text |Cite
|
Sign up to set email alerts
|

Majorana/Andreev crossover and the fate of the topological phase transition in inhomogeneous nanowires

Abstract: Majorana bound states (MBS) and Andreev bound states (ABS) in realistic Majorana nanowires setups have similar experimental signatures which make them hard to distinguishing one from the other. Here, we characterize the continuous Majorana/Andreev crossover interpolating between fully-separated, partially-separated, and fully-overlapping Majorana modes, in terms of global and local topological invariants, fermion parity, quasiparticle densities, Majorana pseudospin and spin polarizations, density overlaps and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 150 publications
0
6
0
Order By: Relevance
“…It led to the hard SC gap induced by the proximity effect [7,8] and allowed to approach the theory predicted 2G 0 -height (G 0 = e 2 /h-the conductance quantum) of the zero-bias peak [9][10][11]. In spite of these advantages the nearly quantized peaks measured in the experiments are not sufficiently stable upon the variation of gate voltage and magnetic field [10,12] and can be related to the presence of trivial Andreev bound states which are rather ubiquitous in the inhomogeneous wires [13,14]. Moreover, other transport peculiarities related to the Majorana excitation have not been observed in practice yet.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…It led to the hard SC gap induced by the proximity effect [7,8] and allowed to approach the theory predicted 2G 0 -height (G 0 = e 2 /h-the conductance quantum) of the zero-bias peak [9][10][11]. In spite of these advantages the nearly quantized peaks measured in the experiments are not sufficiently stable upon the variation of gate voltage and magnetic field [10,12] and can be related to the presence of trivial Andreev bound states which are rather ubiquitous in the inhomogeneous wires [13,14]. Moreover, other transport peculiarities related to the Majorana excitation have not been observed in practice yet.…”
Section: Introductionmentioning
confidence: 82%
“…In order to treat the transport problem analytically we first address to the Kitaev model at the symmetric point, t = Δ and μ = 0. Employing the Majorana-operator representation, a j = 1 2 γ jA + iγ jB , where γ jA,B = γ + jA,B , one can rewrite the device Hamiltonian (14) in the form…”
Section: A1 the Symmetric Kitaev Chainmentioning
confidence: 99%
“…Therefore, when the rotation rate of the one-dimensional helical chain is nonuniform, the above mapping is to an effective Hamiltonian that is reminiscent of a one-dimensional semiconductor nanowire with spatially varying parameters. Such nanowires have been considered extensively and it has been shown that trivial zero-energy Andreev bound states (ABSs) are abundant in these systems [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Theory Of a One-dimensional Spin Chain With Spatially Varyin...mentioning
confidence: 99%
“…In fact, it was shown that trivial Andreev bound states (ABSs) [49,50] are expected to be abundant in nanowires [38]. These trivial states can also result in zero-bias peaks which mimic MBSs and they occur, for instance, due nonuniformities in the nanowire parameters [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Despite several further signatures of MBSs being proposed, due to the high prevalence of possible zero-energy modes, it remains unclear if a conclusive measurement of MBSs can be performed in nanowire systems.…”
Section: Introductionmentioning
confidence: 99%
“…It led to the hard SC gap induced by the proximity effect [7,8] and allowed to approach the theory predicted 2G 0 -height (G 0 = e 2 /h -the conductance quantum) of the zero-bias peak [9,10,11]. In spite of these advantages the nearly quantized peaks measured in the experiments are not sufficiently stable upon the variation of gate voltage and magnetic field [10,12] and can be related to the presence of trivial Andreev bound states which are rather ubiquitous in the inhomogeneous wires [13,14]. Moreover, other transport peculiarities related to the Majorana excitation have not been observed in practice yet.…”
Section: Introductionmentioning
confidence: 98%